Special topics in structural dynamics. Volume 6 : proceedings of the 35th IMAC, a Conference and Exposition on Structural Dynamics 2017 - Dervilis, Nikolaos (Conference proceedings of the Society for Experimental Mechanics series., 2017)
Special Topics in Structural Dynamics, Volume 6: Proceedings of the 35th IMAC, A Conference and Exposition on Structural Dynamics, 2017, the sixth volume of ten from the Conference brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on: Experimental Methods Analytical Methods General Dynamics & Modal Analysis General Dynamics & System Identification Damage Detection.